Extraction and Characterization of Tunisian Quercus ilex Starch and Its Effect on Fermented Dairy Product Quality - Youkabed Zarroug; Mouna Boulares; Jamel Mejri; Bechir Slimi; Ghaith Hamdaoui; Saida Djebi; Fatma Saidi; Hanen Nasri; Dorra Terras Sfayhi; Mohamed Kharrat (International Journal of Analytical Chemistry)
In this study, a new starch has been isolated from acorn (Quercus ilex) fruits. The chemical composition of acorn flour showed its richness in carbohydrates (64.43%), proteins (8%), and fat (10%). The extraction yield of acorn starch was about 34.5%. Thus, the composition of extracted acorn starch and its physical and functional properties were studied. Acorn starch had high purity represented by low proportions of proteins (0.92%) and lipids (0.51%) with a pH of 5.3. The swelling power was 20.76 g/g, while the solubility was about 64.22% at 90°C which suggests that acorn starch has potential for use in food industries. The FT-IR spectra of isolated native starches have shown the main bands characterizing the starch. However, X-ray diffractograms exhibited an A- and B-type diffraction pattern. Furthermore, the effect of acorn starch incorporation at different levels (0.5%, 1%, 1.5%, and 2%) on the quality parameters of a fermented dairy product was investigated at the beginning of storage. The results demonstrated that the most suitable dose of acorn starch to be incorporated in the fermented dairy product was lower than 1%. This low concentration reduced syneresis, improved functional properties, and enhanced the viscosity of the fermented dairy product.